Características estruturais e morfogênicas de culturas de Interesse Zotécnico - Anderson Ramires Candido (2023)
Millet stands out as an alternative to be grown in different types of climate and soil. Due to its flexibility of use, rusticity, tolerance to low fertility soils, water deficit and periods of veraison, characteristic of the Cerrado regions, as well as its good production of green and dry mass. The aim of this study was to i) select millet (Pennisetum sp) hybrids that have potential for silage; and ii) compare the selected hybrid to traditional crops (corn and sorghum) for silage. The experimental period comprised two agricultural years 20/21 and 21/22, during the rainy season. The experimental design was in randomized blocks, in a 3 (hybrids or crops) x 2 (years) factorial scheme, where: experiment i) three millet hybrids BAMH 210076, BAMH 210015 and ADRf 6010; and, experiment ii) three crops, maize KWS 9555, sorghum BRS 658 and millet ADRF 6010 Valente, both with four blocks. As a result, in experiment (i), the ADRf 6010 hybrid was found to have high dry mass and green mass yields, and consequently more leaf and stalk mass, and that the plant height (PH) variable can be indicative of the production estimate when choosing between millet hybrids. In experiment (ii), millet produced more green and dry mass compared to maize and sorghum, which indicates that the crop suffers less from climate change during its development.